Detection of neocarzinostatin chromophore-deoxyribose adducts as exonuclease-resistant sites in defined-sequence DNA - Povirk, Lawrence F.; Goldberg, Irving H. (Biochemistry (Easton), 1985)
A 5'-end-labeled DNA restriction fragment was treated with the nonprotein chromophore of neocarzinostatin under anoxia in the presence of dithiothreitol, conditions known to maximize formation of chromophore-deoxyribose adducts. Under conditions where unmodified DNA was digested to completion, chromophore-treated DNA was highly resistant to digestion by exonuclease III plus the 3'---5' exonucleolytic activity of T4 DNA polymerase and partially resistant to digestion by exonuclease III plus snake venom exonuclease. The electrophoretic mobilities of the products of exonucleolytic digestion suggested that (i) digestion by exonuclease III or T4 polymerase terminated one nucleotide before the nucleotide containing the adduct, (ii) the remaining nucleotide directly adjacent to the adduct (3' side) could be removed by snake venom phosphodiesterase, but at a slow rate, (iii) the covalently linked chromophore decreased the electrophoretic mobilities of the digestion products by the equivalent of approximately three nucleotides, and (iv) adducts formed under anaerobic conditions occurred at the same nucleotide positions as the strand breaks formed under aerobic conditions (primarily at T and, to a lesser extent, A residues). The close similarity in sequence specificity of adducts and strand breaks suggests that a common form of nascent DNA damage may be a precursor to both lesions. A chromophore-induced free radical on C-5' of deoxyribose, subject to competitive fixation by addition reactions with either oxygen or chromophore, is the most likely candidate for such a precursor. The base specificity of adduct formation does not reflect the reported base specificity of neocarzinostatin-induced mutagenesis, suggesting that lesions other than adducts may be responsible for at least some neocarzinostatin-induced mutations, particularly those occurring at G X C base pairs.